Academic Performance and Cognitive Load in Mobile Learning - Zhampeissova, Korlan; Gura, Alena; Vanina, Ekaterina; Egorova, Zhanna (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The study considers the influence of cognitive load on the achievement of educational goals in the concept of mobile learning. It has been proved that the effectiveness of educational programs in a mobile learning environment is achieved by harmonizing cognitive load and structuring the educational content. The experiment was performed in order to identify pedagogical tools to ensure the effective use of the mental resources of students and to reduce their cognitive load when studying educational materials. The experiment was performed within the course of National education as part of the educational programs of Sechenov First Moscow State University (Russia) and Abai Kazakh National Pedagogical University (Kazakhstan). Traditional classroom learning was supplemented with electronic educational resources and a mobile learning program developed based on the Storage ISpring Cloud mobile learning platform with a focus on the study of national values of good manners and education. The experimental groups were offered three different approaches to studying the discipline in a mobile learning environment. The observation of the learning process helped us to identify the key aspects of effective educational practice in a mobile learning environment, namely: high-quality educational content; thematic and temporal structuring of the educational process; distribution of cognitive load in the educational course; introduction of tools to encourage student attention; active participation of students in the educational process; synergy of knowledge accumulation and delivery in the learning environment; thematic social interaction of the members of the educational group. The results of the experiment confirmed the constructive influence of pedagogical tools aimed at the reduction of cognitive load of students on the effectiveness of educational programs in a mobile learning strategy.